Medicine and Empathy in Contemporary British Fiction - Whitehead, Anne (Edinburgh University Press, 2017)
This book marks a critical intervention in the medical humanities that takes issue with its understanding of empathy as something that one has
Description based on publisher supplied metadata and other sources
Keywords: English fiction-21st century-History and criticism; Empathy in literature; Medicine in literature; Psychology in literature; Medizin; Englisch; Geisteswissenschaften; Sprechende Medizin; Einfühlung; Literatur